Small-scale variation of ammonia oxidisers within intertidal sediments dominated by ammonia-oxidising bacteria Nitrosomonas sp. amoA genes and transcripts - Duff, Aoife M. (Sci Rep, 2017)
While numerous studies have investigated the abundance of ammonia oxidising bacteria and archaea (AOB/AOA) via the ammonia monooxygenase gene amoA, less is known about their small-scale variation and if amoA gene abundance equates to activity. Here we present a spatial and temporal study of ammonia oxidation in two small intertidal bays, Rusheen and Clew bay, Ireland. Potential Nitrification Rate (PNR) was ten-fold higher in Rusheen bay (Clew: 0.27 ± SD 0.55; Rusheen: 2.46 ± SD 3.4 NO(2) (−) µg(−1) g(−1) day(−1), P < 0.001) than in Clew bay but amoA gene abundances were similar between bays, and comparable to those in other coastal ecosystems. Within bays AOB genes increased towards the muddy sediments and were positively correlated with PNR and pH. Less spatial variation was observed in AOA abundances which nevertheless positively correlated with pH and temperature and negatively with salinity and ammonia. Transcriptionally active AOB and AOA were quantified from all sites in Rusheen bay, February 2014, following the general trends observed at DNA level. AOB phylotypes predominantly from the known Nitrosomonas group were distributed across the bay, while Nitrosomonas group B phylotypes were absent from low salinity sites. AOA genes and transcripts were primarily affiliated with Thaumarchaeota group I.1a.